WHY ADULT VIEWS MATTER: SCHOOL PERSONNEL PERSPECTIVES ABOUT CHILD SCHOOL PARTICIPATION - Eduardo A. Lugo - Hernández (Revista Puertorriqueña de Psicología, 2016)
Community-Based Participatory Research promotes the inclusion of diverse voices in the research process and in decision-making processes. However, there are very few research studies that collaborate with children, especially within the context of schools. Promoting child participation has benefits both for children as well as for schools. Nonetheless, this may depend on how adults react to such participation. The present study is part of a broader study on school violence prevention. Our objective is to explore school personnel’s concept of childhood and how it relates to their opinions about child school participation. We conducted a discussion group with nineteen (19) faculty and non-faculty members of a public school to ask them questions about the topic. We categorized participants’ answers and analyzed relationships among them. Results suggest that participants’ concept of childhood is linked to socio-cultural and historical factors and that it impacts their opinions about child participation. Also, school personnel recognize that child participation has benefits for children, the school and the wider society. This contrasts with deficiencies on how to articulate this participation beyond traditional classroom strategies. We discuss the implications of these results for pedagogical practice and for participatory research as promoters of children voices in context.